Use of energetic resources in sheep-pig farms in dehesas of south-west Extremadura - Pulido García F.; Escribano Sánchez M.; Mesías Díaz F.J.; Rodríguez de Ledesma A. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
Dehesas are farm systems that cover with their own resources a great deal of the livestock's food needs. This paper deals with the group of factors that influence the use of grazing resources in typical dehesas of Southwest Extremadura. In the analyzed dehesas, the territory covers up to 73 per cent of sheep's food needs, although this value is only 47 per cent for the 'Iberian' pig. From this study we can state that the knowledge of energetic food flows is an interesting starting point to analyze the management and the sustainable use of dehesas' resources.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)